"The very ugly duckling" meets Minecraft: identity work and interpretive competence. (17th February 2019) - Wilson, Sue; Rennie, Jennifer
Abstract: Picturebook discussions are commonplace literacy events in contemporary classrooms. The different experiences, backgrounds and ways of being that individual students draw upon during talk around texts prompt a broad range of ways to make, negotiate and share meanings. In addition to developing students' literacy skills such as oral language, vocabulary and comprehension, these discussions have been shown to be instrumental in developing students' interpretive competence which is important for achieving learning outcomes. In this article, we report a study that investigated how four diverse groups of 10‐ and 11‐year‐old students and teachers from two schools experienced such reading events. The study found that making sense of these books was more productive when students were given permission to switch identities and make connections to their out‐of‐school cyber and popular culture worlds. Using discourse analytic techniques, we uncover the identity work during a number of discussions around two different picturebooks and show how this enabled these learners to enter the academic space and demonstrate interpretive competence.